Reading and comprehension: phoniatric assessment in students with reading difficulties - Vanessa Magosso Franchi; Mônica Elisabeth Simons Guerra; Beatriz Cavalcanti Albuquerque Caiuby Novaes; Mariana Lopes Favero; Sulene Pirana (Brazilian Journal of Otorhinolaryngology, 2023)
Introduction: Reading is a highly refined skill that encompasses two main components: decoding graphic symbols and understanding the written message. These aspects generally develop together, but reading comprehension is a much more complex process, sustained not only by the identification of written words and vocabulary but also by language systems, such as syntax and general knowledge. Although there is a well-established technique for performing the phoniatric assessment, there is no common use of tests that assess reading comprehension or the association of this information with other assessment data. Objective: The objective of this study is, in the context of the phoniatric consultation, to evaluate the reading and retelling in children with relevant reading difficulties and to correlate the decoding and comprehension problems with the alterations observed in auditory and visual perceptual tests, pointing out the evidence that best contributed to the differential diagnosis of these subjects. Methods: Starting from a population of 301 children enrolled in the 4th and 5th grades of elementary school, 13 children with evident reading and writing difficulties were evaluated regarding the reading and retelling tasks and separated into groups according to the problem of decoding, fluency, and comprehension. Reading performance was correlated with the performance in visual and auditory perceptual tests and based on the similarity analysis, the tests considered to be the most relevant in the diagnosis process of these children were identified. Result: The results suggest that the tasks: naming of figures, repetition of numbers in reverse order, figure copying, syllabic synthesis, phonemic synthesis, rhyme, and phonemic manipulation altogether contribute to diagnosis and multidisciplinary intervention aspects. Conclusion: Some tasks are more relevant to the diagnostic process of children with complaints of learning difficulties in reading.